BRAND IMAGE AND PERCEIVED QUALITY ON CONSUMER BUYING DECISION OF SAMSUNG MOBILE PHONE IN MANADO - Maindoka, Raiza; Lapian, Joyce; Tumewu, Ferdinand (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Buying decision is the stage in which consumers make the decision or take an action whether to purchase a certain product or not. The purpose of this research is to analyze the simultaneous effect of brand images and perceived quality of consumer buying decision. This research, the population refers to people in the city of Manado which used mobile phone brand Samsung with sample size as many as 100 respondents. This research used quantitative analyze by using questionnaires and used Multiple Regression Analysis. Result and conclusion show that brand image and perceived quality have significant effect on consumer buying decision while in the case of simultaneous effect. Brand image has a significant partial effect on consume buying decision while perceived quality has no significant partial effect on consumer buying decision and to analyze the simultaneously and partially effect on consumer buying decision, and it is better to use brand image variable to measure consumer buying decision. Therefore, further studies should widen the variables that can potentially effect consumer buying decision and broaden the scope of respondents not only in the region of Manado, but also can use comparative analysis with surrounded cities of Manado. Keywords: brand image, perceived quality, buying decision